Brachiaria híbrida (syn. Urochloa híbrida) sob distintas estratégias de corte - Pinheiro, Jairo Gonçalves (2017)
The work was developed with the aim of characterizing the brachiaria hybrid, submitted to different pre and post cut conditions for forage canopy maintenance in different grazing methods and different conditions of forage canopy maintenance. The experiment was conducted in the forage sector of the Federal University of Uberlândia in 2015. For evaluation of brachiaria hybrid was used a completely randomized design with 36 plots, in three management protocols, 12 plots with 4 treatments and 3 replications. In the intermittent stocking, treatments 10, 15 and 20 of post-cut height were established and both under conditions of 95% of pre-cut light interception and treatment Fixed / 15 cuts every 28 days in the waters and 56 days in the dry ones with 15 cm Simultaneously. In the continuous stocking the treatments were plots maintained at 10, 20, 30 and 40 cm of height respectively. For the deferment, the initial heights were used the same maintained in the continuous stocking differing the parcels by a period of 100 days. According to the data the treatment 20 had a lower production of forage. Treatment 30 had the lowest stem yield over treatment 10. Treatment 40 had a higher standard of FP responses compared to treatment 10 and a higher standard of response in PL compared to treatment 10 and 20. In the delay there was no difference Among treatments in the evaluated parameters. The plots submitted to the treatment 20 presented lower forage yield and stem yield during the water period. In the droughts, the plots submitted to the treatment 10 had the pattern of response to leaf production lower than the other treatments. Treatments 30 and 40 had the percentage of crude protein in the bromatological composition similar in the water period. The bromatological composition in the dry season did not differ between treatments. According to the proposal, the management strategies of the brachiaria hybrid interfere in the morphological characteristics in the different pre and post cut conditions.